Comparison of three different extenders on Murrah buffaloes (Bubalus bubalis) semen freezability. (10th May 2017) - Zorzetto, M. F.; Martin, I.; Sancler‐Silva, Y. F. R.; Zoca, S.; Freitas‐Dell'Aqua, C. P.; Papa, F. O.; Ramos, A. A.; Nunes, J. F.; Salgueiro, C. C. M.; Oba, E.
Summary: The use of frozen semen for artificial insemination is the main approach utilised for the genetic improvement of most domesticated species. The advantages include lower transportation costs, continuous availability of semen, fewer occurrences of sexually transmitted diseases and the incorporation of desirable genes in a relatively short amount of time. Nevertheless, the use of frozen semen in buffalo herds remains limited due to the loss of sperm quality when buffalo semen is frozen. So, the goal of this study was to evaluate the pre‐ and post‐cryopreservation quality of buffalo semen diluted in three distinct freezing media: Tris‐egg yolk, Botu‐bov® (BB) and ACP‐111®. Thirty‐two ejaculates from four bulls were analysed in terms of kinetics, morphology and sperm viability by epifluorescence microscope. Thawed samples were also evaluated for capacitation‐like damage, DNA fragmentation and plasma and acrosomal membrane integrity using flow cytometry. The Tris‐egg yolk and BB® extenders yielded better results than the ACP‐111® extender for kinetics parameter (total motility, progressive motility and percentage of rapid cells). However, semen samples were similar for parameters evaluated by flow cytometry. Taken together, the data indicate that in comparison with Tris‐egg yolk and BB extender, ACP‐111® can also be used as an extender for buffalo semen cryopreservation.